Design and Build IoT Smart Home System with Blocks Based App Inventor Programming - Agus Suharto (Postgraduate, University of Mataram, 2025)
IoT adoption and integration has increased over the past few years due to the increasing consumer demand for convenience, security, and energy savings, creating opportunities for us to interact with our surroundings by integrating physical devices through IoT. Fundamentally, the Internet Society cares about IoT because it is an evolving aspect of how people and institutions are likely to interact with the Internet in their personal, social, and economic lives. MIT App Inventor is an intuitive visual programming environment that allows anyone to build applications including IoT for Android/iOS phones or tablets. Although a number of block-based approaches are available to program some IoT hardware, it is still an area that has not been widely explored. In this study, we will discuss how to implement IoT Smart Home with a block-based programming approach using MIT App Inventor. The application development method uses the ADDIE method with stages, namely Analysis, Design, Development, Implementation, Evaluation. The results of the research evaluation using the EUCS method with dimensions of Content, Accuracy Ease of Use, Format, Timeliness, the results obtained in the study average indexes of 79.80%, the hope for future research is how blocks based can inspire people to be creative with IoT so that beginners can build mobile applications integrated with IoT technology.